2011
DOI: 10.3109/0284186x.2011.558522
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy for abdominal targets using volumetric intensity modulated arc therapy with RapidArc: Feasibility and clinical preliminary results

Abstract: (2011) Stereotactic body radiation therapy for abdominal targets using volumetric intensity modulated arc therapy with RapidArc: Feasibility and clinical preliminary results, Acta Oncologica, 50:4, 528-538,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 38 publications
3
51
0
2
Order By: Relevance
“…OAR sparing was better with IMRT and VMAT compared with CRT. Scorsetti et al [154] reported on early clinical results with VMAT (RapidArc, Varian) in the treatment of primary or metastatic tumours at abdominal sites, which showed promising results in terms of local control and acute toxicity rates. An important factor to consider in intra-abdominal radiotherapy is the effect of intrafraction motion, which can reduce the accuracy of treatment, and methods to account for this should be considered.…”
Section: Intra-abdominal Tumoursmentioning
confidence: 99%
“…OAR sparing was better with IMRT and VMAT compared with CRT. Scorsetti et al [154] reported on early clinical results with VMAT (RapidArc, Varian) in the treatment of primary or metastatic tumours at abdominal sites, which showed promising results in terms of local control and acute toxicity rates. An important factor to consider in intra-abdominal radiotherapy is the effect of intrafraction motion, which can reduce the accuracy of treatment, and methods to account for this should be considered.…”
Section: Intra-abdominal Tumoursmentioning
confidence: 99%
“…28 Numerous other published trials have also looked at the role of SBRT in the treatment of locally advanced pancreatic cancer. [29][30][31][32][33][34][35][36] In Table 1, we present a selected number of studies addressing this topic.…”
Section: Clinical Outcomes In Patients Treated With Sbrtmentioning
confidence: 99%
“…Ennek megfelelően az utóbbi években egyre több közleményt és összefoglalót találhatunk a szakirodalomban az úgynevezett hipofrakcionált "test" (koponyán kívüli) stereotaxiás kezelésekről (stereotactic body radiotherapy -SBRT). Az előzőekben taglalt betegségtípusok nyirokcsomó-, csont-, tüdő-, mellékvese-és májáttétei-nek sugárkezelése kapcsán számtalan centrum és munkacsoport írta le a saját eredményeit [3,7,9,16,17,18,19,20]. Intézetünk ez irányú első tapasztalatait egy má-sik közleményben tervezzük közzétenni hamarosan.…”
Section: Megbeszélésunclassified
“…Kifejezetten hasi-kismedencei áttétek stereotaxiás kezelésével kapcsolatban is találhatunk klinikai közlemé-nyeket, bár ebben a régióban is elsősorban frakcionált kezelési formákat alkalmaztak a különböző orvosi csoportok betegeik többségénél [16,17,18,20]. Perkins és mtsai 20, különböző hasi és kismedencei áttétes daganatban szenvedő betegnél, egyszeri 18 Gy medián dózis alkalmazásával, mindössze grade 1-2 mellékhatások mellett, 48%-os válaszadási arányt értek el [8].…”
Section: áBraunclassified